Unexpected side effect in mCRC: A care-compliant case report of regorafenib-induced hyperammonemic encephalopathy. Issue 16 (April 2017) - Quirino, Michela; Rossi, Sabrina; Schinzari, Giovanni; Basso, Michele; Strippoli, Antonia; Cassano, Alessandra; Barone, Carlo
Abstract: Rationale: Regorafenib represents a treatment option in heavily pretreated patients affected by metastatic colorectal cancer (mCRC). Its safety profile is typical of small-molecule tyrosine-kinase inhibitors (TKIs) and most adverse events are manageable. Patient concerns: A 56 years-old Caucasian man affected by mCRC with normal hepatic reserve was treated with regorafenib as second-line treatment. After only 2 days of therapy, the patient presented to the emergency department due to impairment of both spatial and temporal orientation and motor function with bradylalia. Interventions: Serum ammonia level was 191 mmol/L, liver function tests and complete blood count were normal. Regorafenib was withheld and branched chain amino acids and lactulose were administered. Outcomes: Serum ammonia level returned within the normal range, but when regorafenib was restarted at a lower dose level, a new episode of acute confusion arised. Main lesson: Discontinuation of regorafenib after confirmation of hyperammonemia is strongly recommended; reintroduction of the therapy at lower doses after resolution of symptoms related to hyperammonemic encephalopathy has to be discouraged.